SUPPORT OF THE PHK PROGRAM IN IMPROVING CHILDREN'S EDUCATION IN TUMU VILLAGE EAS NUSA TENGGARA - Nova Elny I Pobas (SocioEdu: Sociological Education, 2022)
This study aimed to determine the support of the PKH program in improving children's education, and the impact of the PHK program in improving children's education in Tumu Village, North Amanatun District. This research was qualitative research that was intended to understand in depth the support of the PHK program in improving children's education. The subjects of this study were children and parents. Data were collected through observation, interviews, and documentation. Data analysis techniques were data collection, data reduction, data display, and conclusion drawing/verification. The research was carried out in Tumu Village, North Amanatun District. It was found that the PKH program cooperated with the village apparatus and every child receiving the PHK who was still in elementary, junior high, and high school was always monitored for progress by checking and asking for routine attendance. Students were taught at school by doing these checks, the PKH program knows the progress of the participants so that they can receive the assistance PKH properly. The impact is that it can help underprivileged children to get a good education, however (PKH) which should be used for education costs, many misuse it for their daily needs and still always hope for assistance. As a result, they are lazy to work.